Audit E-Signature Public Service Project Using Knowledge Quality Management - Gde Brahupadhya Subiksa; Kadek Ary Budi Permana; Made Sudarma (Doctorate Program of Engineering Science, Faculty of Engineering, Udayana University, 2017)
Management Information System Project (E-Signature) is a collaborative project between the Department Investment and Integrated Service Denpasar City with Institute for Research and Community Service of Udayana University. This project is commenced on 21 April 2017 and must be completed on 21 August 2017, the project is supervised and controlled directly by the Section Data Processing and Investment Information System. The plan of this project will be launched in January 2018. Before the system is launched and used by permit applicants and related officials, we need to have an audit on the quality of project management. To measure the quality of project management we used one of the knowledge in the Project Management Body Framework of Knowledge (PMBOK) that is Management Quality Project. We also use Capability Maturity Model (CMM) to help define the maturity level of information systems management. With this we can know the quality of Project Management Information System Management License (E-Signature) at the Department Investment and Integrated Service Denpasar City and provide recommendations or information related to the results of the audit we have done.